Influence of Manual Therapy and Stretching Exercises on Mobility Status and Pulmonary Function Tests Among Patients with Ankylosing Spondylitis - Daniel Szewczyk; Teresa Sadura-Sieklucka; Beata Tarnacka; Tomasz Targowski (Rehabilitacja Medyczna)
Introduction: AS (ankylosing spondylitis) is a systemic disease that impairs entire body functioning of a patient. The most common dysfunctions concern the area of the chest, spine and upper limb. As a consequence of these dysfunctions, the lungs of patients work in abnormal conditions, impairing their functioning.Objectives: The aim of the study is assessing the impact of rehabilitation among patients with AS on functional and respiratory parameters.Material and methods: The study comprised 45 patients divided into two groups. For 25 patients in the group rehabilitation was focused on manual therapy (TM) while 20 patients were rehabilitated on the basis of stretching exercises (SE). As part of improvement progress assessment, the following were measured: upper limb mobility, chest expansion, Occiput to Wall Distance test, spinal angle, functional examination of the respiratory system, the Bath AS Disease Activity Index (BASDAI), Bath AS Functional Index (BASFI) and Pain Disability Index (PDI) questionnaires.Results: After rehabilitation, the Occiput to Wall Distance test also improved expansion of the chest. The BASDAI, BASFI, questionnaires and the VAS scale improved in both study groups. Among respiratory parameters, inspiratory and respiratory muscle strength further increased.Conclusions: Rehabilitation is a very effective form of improving the patient's functional status and should be an indispensable element of the patient's treatment. Both manual therapy and stretching exercises have been shown to be successful.